Factor affecting the continuation of temporary contraceptive among married women aged 15-49 years in bode of Thimi. - Shrestha, Shyam Lal (2000)
ABSTRACT: A descriptive study was conducted in Thimi Muncipality, Bode, Bhaktapur from 2 Febrary to 5 May 1999 with the aim to identify the factors (socio-economic, demographic, health service and motivating) affecting the continuation of temporary contraceptive practice among married women at reproductive age MWRA (15-49 years). One hundred any thirty MWRA, who practices temporary contraceptive method, were interviewed by using structured questionnaire. The investigator selected the Thimi Municipality Bode - Bhaktapur in Rajbahak Community to collect data and conduct quantitative investigation. Total MWRA were taken sample through household survey method. The structured and tested questionnaires were asked with respondents, which were based on Demographic, Socio-Economic and Educational, Health Service and Motivating Factors. These all factors are associated with objective. Collected data were analyzed systematically and interpreted them simple statistical way such as number, percentage and shown in simple pie-chart as well as simple bar-graph. It is found that the use of temporary contraceptive methods by MWRA, the DMPA has the highest in percent ( 46.92 percent) followed by oral Pills (27.69 percent) and Norplant (16.92 percent). One of 130 MWRA who use the temporary contraceptive methods in Rajbahak community-Bode-8, Thimil Muncipality Bhaktapur, 78 (60 percent) MWRA wanted to discontinue & change the existing temporary contraceptive methods due to various problems and only 52 (40 percent) wanted to continue these temporary contraceptive method. Maximum number of respondents and husbands are shown in elementary literacy status (60 percent and 82.30 percent), so on occupation site, most of the respondents and husbands are concerned in farmer and labour (62.30 percent and 52.38 percent) and according to source of income, 52.30 percent are under 5000 Rs. per months. According to above data, life stander is low in that community. Respondents who have gotten positive attitude and support to application of temporary contraceptive method, they have encouraged to continuation these practice. Some of the respondents, (29.23 percent) who want to another baby, they want to discontinue and some are wanted to change the existing method (24.35 percent) due to long distance to take service. So on some respondents (17.69 percent) have wanted to discontinue the existing method due to lack of husband's support.